La pesquería de Penaeus stylirostris (Decapoda: Penaeidae) en el Golfo de Nicoya, Costa Rica - Palacios, J A (1996)
A cohort analysis was perfonned for Penaeus stylirostris Stimpson, 1871 in the inner Gulf of Nicoya. Overfishing is evident for males 150-160 mm and in females over 170 mm in length. These groups also showed the highest instantaneous mortality cates. Higher catches are for sizes 130-140 mm. The small-scale fishing fleet reportedIy caught 29 457 Kg of white shrimp (Penaeus occidentalis Streets, 1871 y P. stylirostris) equivalent to US $ 558 210. During August 427 708 kg of shrimp were caught in a I 378 days fishing effort; a standardization factor of 0.5. was revealed for the small-scale fishing fleet effort. The highest capture percentage for Penaeus occidentalis was 55.06